2014
DOI: 10.15197/sabad.1.11.83
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Mean Platelet Volume in Children with Juvenile Idiopathic Arthritis

Abstract: Juvenile idiopathic arthritis (JIA) is the most common chronic inflammatory arthritis in children. Mean platelet volume (MPV) is an indicator of platelet size and has been investigated as an inflammation marker in several diseases MPV, ESR, and CRP in the JIA group (r=0.676, p<0.001 and r=0.430, p<0.006). In addition, a negative correlation was found between platelet count and MPV (r= -0.818, p<0.001

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…This comes in agreement with Unsal et al [23] and Özdoğan et al [30] who found a predominance of males among JIA patients. On the contrary, many studies reported a higher incidence of JIA in females than males [31,32] . This was explained by Thierry et al [28] who concluded that incidence and prevalence vary greatly most probably due to methodological issues, classification used, and time of diagnosis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This comes in agreement with Unsal et al [23] and Özdoğan et al [30] who found a predominance of males among JIA patients. On the contrary, many studies reported a higher incidence of JIA in females than males [31,32] . This was explained by Thierry et al [28] who concluded that incidence and prevalence vary greatly most probably due to methodological issues, classification used, and time of diagnosis.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement with our study, some studies stated that JIA can be associated with growth retardation due to pro-inflammatory cytokines such as IL-6, long-term corticosteroid therapy, malnutrition, and stress (linked to having a chronic illness or disability) [33,34] . In the study done by Sen et al [32] , the most prevalent early-presenting symptoms were arthralgia in 98.1%, fever in 52.1%, fatigue in 39.9%, malaise in 53.5%, and morning stiffness in 15.5%. However, this contradicts Al-Hemairi et al [24] who reported that fever was present in 41.46% of JIA patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation